The Influence Of Janji Jiwa Coffee Product Price And Quality On Buyer Decisions (Study Of Gen Z In Bengkulu) - Riko Tampati; Ida Ayu Er Meytha Gayatri; M. Rahman Febliansa (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
The purpose of this study was to determine the simultaneous influence of price and product quality on purchasing decisions for Kopi Janji Jiwa (a study of Generation Z in Bengkulu). The research method used was a survey, using a questionnaire as the instrument. The regression equation analysis obtained was Ŷ = 5.124 + 0.348X1 + 0.521X2, indicating that price and product quality have a positive influence on purchasing decisions. Thus, an increase in both variables tends to increase Generation Z's decision to purchase Kopi Janji Jiwa in Bengkulu City. The coefficient of determination value of 0.709 indicates that 70.9% of purchasing decisions are influenced by price and product quality, while the remaining 29.1% are influenced by other variables outside this study. The t-test results at a significance level of 0.05 indicate that price and product quality have a significant partial influence on purchasing decisions, while the F-test results at a significance level of 0.00 also prove that both variables simultaneously have a significant influence on purchasing decisions for Kopi Janji Jiwa among Generation Z in Bengkulu City.